2003
DOI: 10.2134/jeq2003.0996
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Removal and Nitrate Leaching for Two Perennial, Sod-Based Forage Systems Receiving Dairy Effluent

Abstract: major contributing source of nitrate (Katz and DeHan, 1996;Berndt et al., 1998). There are 44 000 dairy cows in In northern Florida, year-round forage systems are used in dairy four Florida counties that border the Lower Suwannee effluent sprayfields to reduce nitrate leaching. Our purpose was to River (Florida Agricultural Statistics Service, 2002). quantify forage N removal and monitor nitrate N (NO Ϫ 3 -N) concentration below the rooting zone for two perennial, sod-based, triple-In the LSRW, the types of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The leaching (or downward movement) of nitrate in soil profiles is generally regulated by soil moisture conditions, as well as the balance between the mineralization of soil organic N and N uptake by the crop (Hartemink et al 1996;Woodard et al 2003;Randall and Vetsch 2005). At our experimental site, most of the precipitation (>70% of the annual total) occurred between July and September (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The leaching (or downward movement) of nitrate in soil profiles is generally regulated by soil moisture conditions, as well as the balance between the mineralization of soil organic N and N uptake by the crop (Hartemink et al 1996;Woodard et al 2003;Randall and Vetsch 2005). At our experimental site, most of the precipitation (>70% of the annual total) occurred between July and September (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that soil water NO 3 -N concentration likely to pose ecological problems is primarily the NO 3 -N that escapes plant uptake and moves past the root zone (Woodard et al 2002(Woodard et al , 2003. Despite the differences in the total annual precipitation in 2009 and 2010 (1,044 and 1,222 mm, respectively; Fig.…”
Section: Effects Of Nitrogen Application On Nitrate Leachingmentioning
confidence: 98%
“…Since N uptake efficiency from this treatment was *42%, the data suggest that *58% of the applied N escaped plant uptake, but considering the N application rate it is unlikely that the amount of leached N would significantly contaminate the percolating water. Studies have shown that NO 3 -N leaching is a common occurrence in the sandy soils of southeastern United States, particularly in intensive forage production systems where high N fertilization are used (Woodard et al 2002(Woodard et al , 2003Zotarelli et al 2007;Fan andLi 2009). Fruh (1967) showed that N is one of the most limiting nutrients that causes eutrophication and, consequently, freshwater quality deterioration.…”
Section: Effects Of Nitrogen Application On Nitrate Leachingmentioning
confidence: 99%
See 2 more Smart Citations